Cloud computing solutions in the management of a contemporary business organization. The vendor and user perspective - Ziora, Leszek (Rozwiązania cloud computing w zarządzaniu współczesną organizacją biznesową. Perspektywa dostawcy i użytkownika, 2018)
The aim of the paper is to present the current state of cloud computing solutions application in the management of a contemporary business organization. The author outlined such theoretical aspects of cloud computing solutions as its key concept and architecture, and the benefits resulting from its implementation in contemporary companies and enterprises. The article presents the vendor perspective of cloud computing services utilization in business organizations prepared on the basis of case studies, practical examples and an international research review. The research presenting the user perspective on cloud computing usage was based on the opinions of 100 respondents of cloud computing services and indicated the pros and cons resulting from the implementation and application of this solution which allowed to indicate not only its benefits but also its limitations
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 4 (50), s. 169-177
Keywords: cloud computing; Software as a Service; decision-making support; management information systems; chmura obliczeniowa; oprogramowanie dostępne jako usługa; wspieranie podejmowania dycyzji; systemy informacyjne zarządzania